2005
DOI: 10.1007/s10459-005-4861-0
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Intelligence Medical Education: Measuring the Unmeasurable?

Abstract: The construct of emotional intelligence (EI) has gained increasing popularity over the last 10 years and now has a relatively large academic and popular associated literature. EI is beginning to be discussed within the medical education literature, where, however, it is treated uncritically. This reflections paper aims to stimulate thought about EI and poses the question: Are we trying to measure the unmeasurable? The paper begins with an outline of the relevance and meaningfulness of the topic of EI for docto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
115
0
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(119 citation statements)
references
References 36 publications
0
115
0
4
Order By: Relevance
“…130 During a volunteer intervention, Talarico et al 131 found that EI-focused leadership training did not positively impact resident performance. The finding of mixed outcomes in EI-focused studies is supported by a systematic review that mapped EI to ACGME competencies 132 and by findings from Lewis et al 112 Other studies have focused on the role of EI training for medical students and in assessing medical school applicants. Some have advocated assessing the EI of medical school applicants.…”
Section: Ei Is Desired and Relevant Throughout Medical Education And mentioning
confidence: 92%
See 1 more Smart Citation
“…130 During a volunteer intervention, Talarico et al 131 found that EI-focused leadership training did not positively impact resident performance. The finding of mixed outcomes in EI-focused studies is supported by a systematic review that mapped EI to ACGME competencies 132 and by findings from Lewis et al 112 Other studies have focused on the role of EI training for medical students and in assessing medical school applicants. Some have advocated assessing the EI of medical school applicants.…”
Section: Ei Is Desired and Relevant Throughout Medical Education And mentioning
confidence: 92%
“…Others have questioned this practice based on the variability in measuring EI and on the lack of empiric trials consistently linking EI to outcomes in medicine. 112 As noted in a review 109 and several individual reports, 113 EI has been proposed as part of the curriculum to teach professionalism [114][115][116] and leadership [117][118][119] to trainees and senior physicians. Indeed, models of professionalism have been constructed around EI as a leadership skill.…”
Section: Ei Is Desired and Relevant Throughout Medical Education And mentioning
confidence: 99%
“…To qualify as an intelligence, there must be evidence of stability since the first decade of life; not something assessed on the spot. Several reviews have highlighted the loose definition of EI, which on the one hand, appears to be trainable, so not a form of intelligence, and on the other, appears to be strongly related to personality, which then suggests it is not a measure of aptitude (Lewis et al 2005;Romanelli et al 2006;Davies et al 1998). EI, after all is said and done, appears unrelated to career choice (Borges et al 2009), academic performance (Romanelli et al 2006;Newsome et al 2000) or doctor-patient relationship (Weng et al 2008).…”
Section: Multiple Intelligences Practical Intelligence and Emotionalmentioning
confidence: 99%
“…As a consequence, it is argued that EI should be seen as a more dynamic quality which emerges from the process of sensitive and intelligent problem solving, rather than the sum of individuals' EI. 43 …”
Section: Discussionmentioning
confidence: 99%